FUNGSI KELUARGA DAN GEJALA STRES REMAJA DENGAN LATAR BELAKANG PENDIDIKAN PRASEKOLAH BERBEDA - Widyanti, Lia; Hastuti, Dwi; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
As a period of identity crisis and emotional unstability, instrumental and expressive functions by parents are important key to guide adolescents to achieve their developmental tasks. This study aimed to analyze correlation between instrumental and expressive functions of parents and stres symptoms among adolescent with different background of preschool education. Participants of this study consists of 91 adolescents who graduates from Semai Benih Bangsa (SBB) preschool group (n=31) and formal kindergarten group (n=30), and also adolescent who did not had preschool education background (n=30). The result found that stres symptomps in the third group of adolescent were catogorized as low level. There is significant difference between the three group of adolescent in instrumental function that conducted by parents but theres is no significant difference in expressive function. The stres symptomps of adolescents had negative significant correlation with mother’s age. Meanwhile, family income had positive significant correlation with instrumental function and mother’s age had negative significant correlation with expressive function of parents.